An Investigation into Teacher’s Practice of Jigsaw Technique in Teaching Narrative for Eight Graders of SMPN 1 Menganti (RETAIN, 2013)
This study investigated the practice of Jigsaw technique in teaching English. It sought the answers to the following questions: How did the teacher implement Jigsaw technique in teaching writing narrative text for students of SMP N 1 Menganti? What obstacles did the teacher face in implementation of Jigsaw technique in teaching writing narrative text for students of SMPN 1 Menganti? Has the implementation followed the procedures of Jigsaw suggested by Aronson et al (1978)? This study was limited to one teacher who used Jigsaw technique in teaching writing narrative text in SMPN 1 Menganti following the Jigsaw procedures suggested by Aronson et al (1978). Descriptive qualitative was used in this study. Through semi-structured observation and interview with one English teacher in SMP N 1 Menganti, the data were collected and analyzed qualitatively. It was found that the teacher followed eight of the ten procedures of Jigsaw. She did not give time to students to learn over their segment to become familiar with it and did not give quiz on the material at the end. The teacher also faced some obstacles, such as the use of Bahasa Indonesia by the students and seating arrangement in two groups (home group and expert group). Her voice was so low that it could not be heard by the students clearly. It is concluded that the teacher has modified Jigsaw in teaching writing narrative text suggested by Aronson et al (1978). Key words : Teacher’s practice, Jigsaw, Writing, Narrative Abstrak Penelitian ini menginvestigasi penerapan dari teknik Jigsaw dalam pengajaran Bahasa Inggris. Ini mencari jawaban dari pertanyaan: Bagaimana guru menerapkan teknik Jigsaw dalam mengajar writing narrative untuk siswa SMPN 1 Menganti? Apa kendala yang guru hadapi dalam penerapan teknik Jigsaw dalam pengajaran writing narrative untuk siswa SMPN 1 Menganti? Apakah penerapan dari teknik Jigsaw mengikuti prosedur dari Jigsaw yang disarankan oleh Aronson et al (1978)? Penelitian ini dibatasi pada satu guru yang menggunakan teknik Jigsaw untuk mengajar writing narrative untuk siswa SMPN 1 Menganti mengikuti prosedur dari Jigsaw yang disarankan oleh Aronson et al (1978). Kualitatif deskriptif digunakan dalam penelitian ini. Melalui observasi dan interview semi-studtured dengan satu guru Bahasa Inggris di SMPN N 1 Menganti, data diambil dan dianalisa secara kualitatif. Ditemukan bahwa guru mengikuti delapan dari sepuluh Jigsaw prosedur. Guru tersebut tidak memeri waktu untuk mempelajari tugas bagian mereka agar llebih familiar dan tidak member kuis dari materi pada akhir pembelajaran. Guru tersebbut juga menghadapi beberapa kendala, seperti menggunakan Bahasa Indonesia dengan siswa dan penataan tempat duduk dalam dua grup (home group dan expert group). Suaranya begitu rendah sehingga tidak dapat didengar siswa dengan jelas. Ini disimpulkan bahwa guru telah memodifikasi teknik Jigsaw dalam mengajar writing narrative yang disarankan oleh Aronson et al (1978). Kata Kunci: Praktek guru, Teknik Jigsaw, Menulis, Narrative